Histogenesis of Testicular Parenchyma During Prenatal Life in Buffalo - Kaur,Manjinder (Sociedad Chilena de Anatomía, 2011)
The study was conducted on the testes of 18 buffalo foetii to reveal histogenesis and differentiation of different cells of testicular parenchyma. At 8.0 cm CVR (65 days) the seminiferous tubules were present at gonadal periphery and a network of polygonal mesenchymal cells was seen in the centre of testis. These tubules were surrounded by a distinct basement membrane and a single layer of peritubular cells at 10 cm CVR (74 days), which became double layered at 88.0 cm CVR (272 days). The testicular parenchyma at 12.0 cm CVR had two zones; outer zone having longitudinal tubules and inner zone having rounded tubules. But a reverse pattern of their arrangement was observed at 14.0 cm CVR (92 days). The pre-Sertoli cells were first observed in buffalo foetii of 8.0 cm CVR (65 days) in the periphery of seminiferous tubular epithelium whereas the gonocytes were demonstrable in the centre of tubules at 10.6 cm CVR (76 days). The fetal Leydig cells were also reported at 8.0 cm CVR (65 days) but at 14.0 cm CVR (92 days), the interstitium had considerably expanded due to the differentiation of mesenchymal cells into the Leydig cells.